Evaluation of effective area of air piston gauge with limitations in piston–cylinder dimension measurements. (1st April 2021) - Thakur, Vikas N; Sharipov, Felix; Yang, Yuanchao; Kumar, Sandeep; Ram, Jokhan; Omprakash,; Kumar, Harish; Sharma, Rina; Yadav, Sanjay; Kumar, Ashok
Abstract: The air piston gauge (APG) has been established at the National Physical Laboratory, India (NPLI) for Pascal realization since 2002. The APG at NPLI has been considered a transfer pressure standard because it has been calibrated against the primary pressure standard, i.e. ultrasonic interferometer manometer. As per existing international protocol, the APG establishment as a primary standard, the effective area ( A e ) of piston–cylinder (p – c) assembly and masses must be directly traceable to SI units. We have calculated A e and associated uncertainty of p – c assembly using the theory of rarefaction gas dynamics, which is based on dimension measurements. The value of A e is obtained for varying temperatures and radii of piston and cylinder in their respective uncertainty limits. The variation of the cylinder's inner radius within its uncertainty limit of 0.7 µm includes the expected effective area, i.e. 3.356 775 (5) cm 2 . The effective area's expected values are obtained for the cylinder's radius of 10.338 00 (2) mm, which is approximately 0.65 µm away from the value obtained from dimensional measurements and well within the uncertainty limit. Therefore, to get the effective area of 3.356 775 (5) cm 2, the uncertainty of the cylinder's radius should be at least one order less (similar to piston's radius) than that of the present value. The precision in dimension measurement of the cylinder's internal radius is the critical parameter for effective area calculation of p – c assembly.